2021
DOI: 10.1108/ijshe-06-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Educating prospective teachers for a sustainable gender equality practice: survey design and validation of a self-efficacy scale

Abstract: Purpose This study aims to assess future teachers’ beliefs in their capabilities for sustainable gender equality (GE) practice after graduation and to analyze differences across degree and sex using a self-efficacy scale specifically designed and validated for this study. Design/methodology/approach A survey was administered to three cohorts of undergraduate and graduate student teachers at the University of Alicante, Spain. Using a convenience sample that represented the three teacher majors in early childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In addition, it may be the first time that scalar invariance is found across country and sex in secondary school STEM student teachers, since no studies have been carried out before with this population using the TEGEP. The finding of scalar invariance gives support to previous work by Miralles-Cardona et al [55,60] using the TEGEP with general elementary and secondary education student teachers. A second major finding is that while the Spanish participants had significantly lower gender knowledge and awareness scores than Greek participants, self-efficacy for developing gender attitudes was significantly higher among Spanish than Greek respondents.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In addition, it may be the first time that scalar invariance is found across country and sex in secondary school STEM student teachers, since no studies have been carried out before with this population using the TEGEP. The finding of scalar invariance gives support to previous work by Miralles-Cardona et al [55,60] using the TEGEP with general elementary and secondary education student teachers. A second major finding is that while the Spanish participants had significantly lower gender knowledge and awareness scores than Greek participants, self-efficacy for developing gender attitudes was significantly higher among Spanish than Greek respondents.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, the TEGEP scale had a very high reliability (alpha coefficient for the whole scale was .94 Greek and .95 Spanish samples (.91, .93, and .89 vs .89, .93, and 85 for the subscales, Greek and Spanish, respectively). Previous studies using general education student teachers samples revealed that the scale is reliable and valid [55,59,60]. The scale allows us to obtain individual scores by item, factors, and a total score.…”
Section: Study Design and Instrumentmentioning
confidence: 98%
See 2 more Smart Citations
“…Three papers especially highlight how HEIs contribute to certain SDGs: Dalla Gasperina et al (2021) add the operations element with their research on smart campuses and how they contribute to the SDGs, especially numbers 4 and 9 in Brazil. Whereas Miralles-Cardona et al (2021) focuses on assessing SDG 4.7 and 5 by assessing gender competences within nascent teachers in Spain. Furthermore, Alm et al (this issue) add the student perspective on key competencies related to sustainable development, especially they conclude that real-life experiences enhance interpersonal competencies for sustainability.…”
Section: Editorial To Special Issue On: Assessing the Contribution Of...mentioning
confidence: 99%